1993
DOI: 10.1007/bf00374522
|View full text |Cite
|
Sign up to set email alerts
|

A slowly inactivating transient outward current in rat ventricular myocytes

Abstract: In rat ventricular myocytes we found two components of transient outward current, which could be discriminated time- and voltage- dependently. Besides the well known fastly inactivating transient outward current (ito,f, tau = 35 +/- 8 ms, n = 4) we investigated properties of a slowly inactivating transient outward current (ito,s, tau = 1.7 +/- 0.4 s, n = 4). Because of the slow inactivation process of ito,s tail currents were observed at -25 mV. The inactivation curve of ito,f was characterized by a half- inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
3
10
0
Order By: Relevance
“…The slope factors (K) were -19 mV (i to,s ) and -2 mV (i to,f ). These characteristics, the steeper slope of the i to,f inactivation curve and V 0.5 about 40 mV more positive than that for i to,s , agree with published results (Apkon and Nerbonne 1991;Weis et al 1993). These curve parameters were hardly affected by 10 or 30 µmol/l 17β-estradiol (Table 1).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The slope factors (K) were -19 mV (i to,s ) and -2 mV (i to,f ). These characteristics, the steeper slope of the i to,f inactivation curve and V 0.5 about 40 mV more positive than that for i to,s , agree with published results (Apkon and Nerbonne 1991;Weis et al 1993). These curve parameters were hardly affected by 10 or 30 µmol/l 17β-estradiol (Table 1).…”
Section: Resultssupporting
confidence: 80%
“…In this study the components were termed i to,f (τ inactivation = 34 ms) and i to,s (τ > 1 s). Both components not only differ in their kinetics of inactivation but also have different voltage dependencies of inactivation (Apkon and Nerbonne 1991;Weis et al 1993) and pharmacological sensitivities (Apkon and Nerbonne 1991;Lefevre et al 1991;Weis et al 1995). With respect to 17β-estradiol both components behaved similarly.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, subsequent investigations demonstrated that besides the fast inactivating transient outward current (i to,f ) there exists a second prominent voltagedependently and slowly inactivating outward current i to,s at plateau potentials in rat ventricular myocytes (Apkon and Nerbonne 1991;Lefevre et al 1991;Weis et al 1993Weis et al , 1995. We therefore reinvestigated the effects of tedisamil and focussed our work on the differentiation of i to,f and i to,s and on the respective tedisamil-induced effects.…”
Section: Introductionmentioning
confidence: 99%